Naturally Occurring Diterpenoid Dimers: Source, Biosynthesis, Chemistry and Bioactivities - Lin, Li-Gen; Ung, Carolina Oi Lam; Feng, Zhe-Ling; Huang, Li; Hu, Hao (Planta Medica, 2016)
Diterpenoid dimers are rare in nature and mainly found in higher plants including the families Acanthaceae, Annonaceae, Asteraceae, Calceolariaceae, Chrysobalanaceae, Cupressaceae, Euphorbiaceae, Fabaceae, Lamiaceae, Liliaceae, Meliaceae, Rhizophoraceae, Taxaceae, Velloziaceae, and Zingiberaceae. In addition, a few diterpenoid dimers have been also reported from fungi (Psathyrellaceae), liverworts (Scapaniaceae), and a gorgonian (Gorgoniidae). They feature a wide variety of structures due to different core skeletons, linkage patterns, substituents, and configurations. Accordingly, diterpenoid dimers exhibit a broad range of bioactivities, including cytotoxic, anti-inflammatory, antimicrobial, antimalarial, and antifouling properties, which have attracted more and more research interests in the past decades. This review with 176 metabolites from 109 references provides a comprehensive and up-to-date overview of the source, biosynthesis, structure, synthesis, and bioactivities of diterpenoid dimers.
Keywords: diterpenoid dimers; structure; source; biosynthesis; synthesis; bioactivities